Химический анализ в технологии силикатов - Вакалова Т. В. Татьяна Викторовна; Ревва И. Б. Инна Борисовна; Гурина В. Н. Вера Николаевна; Горбатенко В. В. Виктория Валерьевна (Томск, Изд-во ТПУ, 2007)
В фонде НТБ ТПУ отсутствует